2011
DOI: 10.3329/jhpn.v29i1.7567
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-seeking Behaviour for Common Infectious Disease-related Illnesses in Rural Kenya: A Community-based House-to-house Survey

Abstract: Community surveys of healthcare-use determine the proportion of illness episodes not captured by health facility-based surveillance, the methodology used most commonly to estimate the burden of disease in Africa. A cross-sectional survey of households with children aged less than five years was conducted in 35 of 686 census enumeration areas in rural Bondo district, western Kenya. Healthcare sought for acute episodes of diarrhoea or fever in the past two weeks or pneumonia in the past year was evaluated. Facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
131
8
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 20 publications
12
131
8
1
Order By: Relevance
“…We found no association between male or female headed households in care-seeking for the bivariate analysis. Socioeconomic status has been shown to be positively correlated with care-seeking in other African countries [25,27,[29][30][31]. Wealth quintile was a significant predictor of careseeking in this study for Cambodia and Guatemala, and though the odds were higher for the wealthier quintiles in other countries, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We found no association between male or female headed households in care-seeking for the bivariate analysis. Socioeconomic status has been shown to be positively correlated with care-seeking in other African countries [25,27,[29][30][31]. Wealth quintile was a significant predictor of careseeking in this study for Cambodia and Guatemala, and though the odds were higher for the wealthier quintiles in other countries, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 70%
“…High rates of care-seeking from drug vendors has been reported for malaria especially in Africa [21], and other studies have effectively leveraged this behavior to enhance the skills of private drug retailers to prescribe artemisinin-based combination therapy for children presenting with these symptoms [26]. Another study in rural Kenya reported similar levels of treatment from traditional healers and community volunteers [27]. However, antibiotic treatment for ARI (<40%), and diarrhea (<10%), was much lower in this study, than that reported in the earlier study in Kenya (60%).…”
Section: Discussionmentioning
confidence: 99%
“…12 The field team collected data for all children aged < 5 years in sampled households. For outpatient treatment, the team inquired about costs of registration/visit fees, medicine, transportation, and wage loss.…”
Section: Methodsmentioning
confidence: 99%
“…Geographic accessibility, travel time, waiting time, age, health status, income, service costs, and education are factors shown to be associated with health care use [1][2][3][4][5][6][7][8][9] and improvements in facility physical infrastructure, staffing, and commodity availability and implementation of free highquality healthcare have demonstrated increases in health care utilization. [10][11][12][13] Routine national surveys tend to collect data on individuals' general health care use but often lack specific data on the healthcare service location.…”
Section: Introductionmentioning
confidence: 99%